DAMPAK SOSIAL EKONOMI PADA KELUAGA TENAGA KERJA INDONESIA YANG BEKERJA DI LUAR NEGERI (STUDI KASUS TKI DI MALASIA) - IDA AYU KETUT MARINI; IDA BAGUS EKA ARTIKA; A.A. MADE SURYA KENCANA (Universitas Mahasaraswati Mataram, 2019)
Labor migration from one country to another or migration between countries in the era of globalization has become an increasingly easy phenomenon for workers, because of the various easy accesses that are supported by technology, increasingly supporting regulations and transportation to destenations which more expedite and more affordable. This study aims to determine the social and economic impacts on Indonesian workers families (TKI) from Lombok Island who work in Malaysia. The sample of respondents is 70 families of migrant workers who were working in Malaysia, and interviews are conducted with the wives of the migrant workers. The results show that the families of migrant workers who work in Malaysia actually can improve the quality of social interaction, improve the education level of their children by prioritizing their children's schools, although the negative social impact is also felt by the wives of migrant workers working in Malaysia through Verbal abuse, nicknamed